Comparison of clinical outcomes in clomiphene citrate resistant infertile polycystic ovarian syndrome women after treatment with laparoscopic ovarian drilling (LOD) versus gonadotropins - Rupa, Kumari; Jain, Kanika; Dutta, Debasis; Gupta, Shweta Mittal; Chopra, Kanika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility is the inability of a sexually active, non-contracepting couple to achieve pregnancy in one year. Objective of present study was to compare the clinical outcome of laparoscopic ovarian drilling with gonadotropin ovulation induction in patients with clomiphene resistant Polycystic Ovarian Syndrome. Methods: Present study was a comparative interventional study conducted at the Institute of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, New Delhi for a period of one and a half year. We enrolled 40 clomiphene citrate resistant infertile PCOS women who were undergoing treatment for infertility, after taking written informed consent. The women were randomly divided into two equal groups: one for LOD (laparoscopic ovarian drilling) (group A) and other for gonadotropins (group B). Results: Out of 20, 16 women (80%) in group A ovulated with clomiphene citrate and 18 women (90%) ovulated in group B. Pregnancy was the second major outcome and 4 women (20%) in group A with clomiphene citrate got pregnant and 9 women (45%) got pregnant in group B. Conclusions: Out of 20, 16 women (80%) in group A ovulated with clomiphene citrate and 18 women (90%) ovulated in group B. Pregnancy was the second major outcome and 4 women (20%) in group A with clomiphene citrate got pregnant and 9 women (45%) got pregnant in group B. The treatment option can be selected and tailored according to the individual needs and desires of the patient.